RISING TEACHER COMPETENCE THROUGH LESSON STUDY IN INTEGRATED SCIENCE EDUCATION WITH JELAJAH ALAM SEKITAR APPROACH - Susilowati, Sri Mulyani Endang; Rusilowati, Ani (IJRDO- Journal of Educational Research, 2017)
Sciences teachers in Junior High School are generally Physics and BiologyEducation graduates. Whereas, 2013 curriculum provides Biology and Physics as anintegrated subject, natural sciences. Hence, Physics Education graduates teachers havetrouble in teaching Biology and vice versa. The purpose of this study is to improve theprofessionalism of the science teacher through the lesson study (LS). This research is anaction research conducted in collaboration with the junior high school science teachersand post-graduate students of Science Education and Elementary Education program,Universitas Negeri Semarang. LS determined several topics which will be developed asa sciences learning kit for seventh graders of Senior High School. Implementation of thelearning kit was also implemented by LS. The results showed that LS could improve theteachers’ professionalism that includes the ability of teachers to prepare learning kit,implementing in the classroom using some innovative learning models and assessing thestudents. It is suggested that LS activities need to be developed and implementedconsistently because it is effectively proven to improve the ability of teachers.